Late Quaternary climate change in the north-eastern highlands of Ethiopia: A high resolution 15, 600 year diatom and pigment record from Lake Hayk. (15th December 2018) - Loakes, Katie L.; Ryves, David B.; Lamb, Henry F.; Schäbitz, Frank; Dee, Michael; Tyler, Jonathan J.; Mills, Keely; McGowan, Suzanne
Abstract: Multi-proxy analyses of an 8 m sediment core from Lake Hayk, a closed, freshwater lake in the north-central highlands of Ethiopia, provide a record of changing lake level and inferred regional climatic change for the last 15.6 cal ka years. Between ca. 15.6–15.2 cal ka BP, a lowstand was synchronous with Heinrich Event 1 and an intense drought across Eastern Africa. At ca. 15.2 cal ka BP a lake began to develop at the core site in response to wetter conditions, at the onset of the African Humid Period (AHP). However, in contrast to other lakes in eastern Africa, Hayk lake level fell around ca. 14.8 cal ka BP, indicating a climate shift towards aridity. The lake began filling again at ca. 12.3 cal ka BP and reached maximum water depth between ca. 12.0–10.0 cal ka BP. Lake level declined slowly during the Holocene, culminating in the termination of the AHP at Hayk between ca. 5.2–4.6 cal ka BP. In the late Holocene, ca. 2.2–1.3 cal ka BP, Lake Hayk was again deep and fresh with some evidence of short-term lake level variability. The palaeo-record from Lake Hayk indicates that while it experienced, to a broad degree, the same glacial-interglacial dynamics and sub-millennial shifts in climate found in other palaeolimnological records from eastern Africa, there are offsets in timing and rate of response. These differences reflect chronological discrepancies between records, as well as the varying climate sensitivities and site-specific factors of individual lake basins. This record highlights the different responses by lakes in a climatically vulnerable area of Ethiopia. Highlights: Discrepancies in the timing of the Younger Dryas Stadial proper. No evidence for the catastrophic shift in climate centred at 8.2 ka. Diatom evidence suggesting relatively rapid AHP termination. High-resolution evidence of millennial to multi-decadal variability at Lake Hayk. Regional discrepancies in the timing and expression of climatic events.